Swot Analysis Of General Sharia Savings At Bmt Ugt Nusantara Capem Kencong Jember - Mh Taufiqur Rohman; Muhammad Syarofi; Siti Dwi Nafisah (TIJAROTANA : Jurnal Ekonomi dan Bisnis Syariah, 2026)
One of the strengths of Islamic general savings products at BMT UGT Nusantara Capem Kencong is the existence of a ball pickup system carried out by BMT UGT Nusantara Capem Kencong employees, with this system making it easier for customers to deposit or withdraw cash savings. The purpose of this report is to find out the analysis of general Islamic savings products carried out at BMT UGT Nusantara Capem Kencong with SWOT analysis. This report uses the SWOT Analysis method using data from interviews with BMT UGT Nusantara Capem Kencong employees, literature and field surveys. Based on the results of this report, it explains that this sharia general savings product is in the position of Opportunities and Weakness which shows in the stability strategy (Minimizing internal prob). The strategy carried out is to increase marketing activities (promotion) of Islamic general savings products, maintain the characteristics of BMT UGT Nusantara with a ball pick-up system policy, improve the quality of Islamic general savings products through the application of mudharabah musytarakah contracts that are as good as possible in accordance with Islamic law, add application-based interbank transfer features, and bring up new innovations in accordance with the times.